1992
DOI: 10.1093/mutage/7.4.235
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific distribution of genotoxic effects in mice exposed to cooked food mutagens

Abstract: The induction of organ-specific genotoxic effects of five cooked food mutagens in Swiss albino mice was investigated in microbial animal-mediated assays. The indicator of the induction of DNA damage was a pair of Escherichia coli K12 strains, differing vastly in repair capacity (uvrB/recA versus uvr+/rec+). All compounds gave positive results in the tested dose range between 2.5 and 40 mg/kg body weight (i.p. administration, exposure time 120 min). 2-amino-3,4-dimethylimidazo[4,5-f]quinoline (MeIQ) and 2-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In contrast, AIAs have been shown to induce base substitution and/or deletion mutations in vivo in the lacI or lacZ mutational reporter gene of transgenic mice (187)(188)(189)(190)(191)(192)(193), the colonic crypt cells of mice (194)(195)(196), Dlb-1-specific locus test in mouse small intestine (191,197,198) and the animal-mediated microbial assay system (199).…”
Section: Genotoxicity and Mutagenicity Of Aia-dna Adducts In Vivomentioning
confidence: 99%
“…In contrast, AIAs have been shown to induce base substitution and/or deletion mutations in vivo in the lacI or lacZ mutational reporter gene of transgenic mice (187)(188)(189)(190)(191)(192)(193), the colonic crypt cells of mice (194)(195)(196), Dlb-1-specific locus test in mouse small intestine (191,197,198) and the animal-mediated microbial assay system (199).…”
Section: Genotoxicity and Mutagenicity Of Aia-dna Adducts In Vivomentioning
confidence: 99%
“…Of the 10 pyrolysates identified as the carcinogens, 3-amino-l-methyl-5iT-pyrido[4,3-6]indole (Trp-P-2) is a liver-specific carcinogen (Wakabayashi et al, 1992;Knasmüller et al, 1992), is one of the strongest mutagens (Sugimura, 1985), and occurs frequently in our diet (Yamaizumi et al, 1980). It is very important to mitigate the cancer risk from Trp-P-2 in our daily life, and therefore we have an interest in dietary compounds which can neutralize Trp-P-2.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, 5 mg/kg PhIP is considered a genotoxic dose. It has been shown in earlier studies that PhIP induces bulky DNA adducts in testicular tissue of adult mice and rats at 2.5 to 40 mg/kg bw and 50 mg/kg bw, respectively (Knasmuller et al, 1992; Huber et al, 1997). Similarly, in vivo exposure to other environmental agents such as B(a)P has been shown to give rise to DNA adducts in adult male testicular cells residing within the testis barrier (Olsen et al, 2010; Verhofstad et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…This shows that PhIP was metabolized and reached target organs (Steffensen et al, 2006). Knasmuller et al (1992) reported that PhIP treatment of adult mice induced PhIP–DNA adducts in testicular cells. Our hypothesis is that PhIP treatment leads to the formation of bulky DNA adducts, which, if they remain unrepaired, may interfere with DNA replication and cell division.…”
mentioning
confidence: 99%